A metaheuristic for a numerical approximation to the mass transfer problem - Avendano-Garrido, Martha L.; Gabriel-Argüelles, José R.; Quintana-Torres, Ligia; Mezura-Montes, Efrén (Zielona Góra: Uniwersytet Zielonogórski)
This work presents an improvement of the approximation scheme for the Monge-Kantorovich (MK) mass transfer problem on compact spaces, which is studied by Gabriel et al. (2010), whose scheme discretizes the MK problem, reduced to solve a sequence of finite transport problems.
Keywords: Monge-Kantorovich mass transfer problem; finite dimensional linear programming; transport problem; metaheuristic algorithm; scatter search